Enter and exit: Everyday state practices at Somaliland's Hargeisa Egal International Airport - Tobias Gandrup (Danish Institute for International Studies (DIIS), 2016)
Through an empirical investigation of emerging state practices at Hargeisa Egal International Airport this paper analyses everyday state formation in Somaliland. Taking my point of departure in a recent airport rehabilitation project, I examine emerging security practices and technologies at the airport. Moreover, I provide an analysis that illustrates how Somaliland's state officials and airport management mobilised external resources to finance the rehabilitation project. The main findings of the paper are twofold: on the one hand, the analysis illustrates how emerging state practices at the airport are at once manifesting and anonymising Somaliland as a political entity, while at the same time being part of daily negotiations. On the other hand, it demonstrates that different external resources and historical ties have been mobilised to rehabilitate the airport, thus highlighting how HEIA has become a site where the government of Somaliland seeks and finds international recognition.
Keywords: 300